Atasi Stunting dengan Pemberdayaan Kebun Contoh di Desa Tanarawa, Kecamatan Waiblama, Kabupaten Sikka - Krispina Kara; Maximinus Adrianus Sarto Dumbaris; Modesta Sona; Yasinta Romana; Yohanes Arjunario Flores (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Tanarawa Village, located in Waiblama Subdistrict, Sikka Regency, holds great potential in the plantation and crop sectors despite its hilly and undulating terrain. This potential can be harnessed to enhance the economic well-being of the community while addressing the high stunting rate in the area, where the stunting rate at the Tanarawa Health Center reached 33.5% in 2023. To address this issue, an empowerment program was implemented through a demonstration garden aimed at improving community skills and knowledge in sustainable agriculture. The program included training on the creation of garden beds and the cultivation of nutrient-rich plants such as spinach, water spinach, and mustard greens. The methods used included participatory observation, in-depth interviews, and partnership approaches with local residents. The program successfully provided nutritious vegetables for families, particularly for children affected by stunting, and raised community awareness of the importance of nutritional intake. Additionally, the demonstration garden program offered economic benefits by reducing spending on vegetables and optimizing the use of vacant land.